Dopamine stimulation of phosphatidylcholine (lecithin) biosynthesis in rat brain neurons. - Leprohon, C E (1983)
Rat brain synaptosomes contain enzymes, phosphatidylethanolamine N-methyltransferase(s) (EC 2.1.1.17), that catalyze the methylation of endogenous phosphatidylethanolamine to form its mono-, di-, and trimethyl (i.e., phosphatidylcholine) derivatives. We observe that the activity of these enzymes is enhanced when synaptosomes are incubated with catecholamines: 0.1 mM dopamine increases incorporation of [3H]methyl groups into monomethylphosphatidylethanolamine, dimethylphosphatidylethanolamine, and phosphatidylcholine by factors of 1.7, 1.3, and 2.1, respectively, and 0.1 mM norepinephrine increases [3H]methyl incorporation into monomethylphosphatidylethanolamine and dimethylphosphatidylethanolamine by factors of 1.6 and 2.1, respectively. Stimulation by dopamine, which is observed at concentrations as low as 1 microM, is blocked by haloperidol.